Sexual disorders and personal problems of women aged over 45 - Lew-Starowicz, Zbigniew; Szymańska, Monika (Menopause Review/Przegląd Menopauzalny, 2010)
Aim of the study : To analyse sexual disorders and personal problems in women over 45 years of age. Material and methods : the test population accounted for women over 45 years of age (43% of those aged 45-55 and 57% at the age of 56-70 years), which came to the sexology doctor in 2009 due to sexual disorders and personal problems. Women represented 7.8% of all patients. Results and conclusions : The following sexual disorders dominate: low sexual desire, anorgasmia. But among personal problems, lack of satisfaction with the sexual partner, affairs of their partners and gender identity of their sons prevailed.